Technological System for Improving Physical Performance in Children from 4 to 8 Years Old with High Obesity Rates of Type 1 and 2 Using IoT-Based Wearables in Private Schools in Metropolitan Lima - Espejo-Gonzalez, Alejandro (2024)
According to a study conducted by UNICEF, the main causes of childhood obesity are the high consumption of processed foods and the low amount of physical activity performed by children, generating a higher risk of respiratory, metabolic and cardiovascular conditions. Based on research conducted in different studies, we found that there are not many technologies that monitor and improve the physical performance of children. This paper presents a technological system based on IoT and using wearables to improve the physical performance of children with high obesity rates type 1 and 2. This technological system was verified by conducting a study with 30 children between 4 and 8 years old, evaluating their physical activity and collecting the data obtained from the smartwatch. This study showed, according to the conclusions found, that it is a useful tool for the collection of data required by specialists and easy to use for children and their parents. In addition, it is a means to overcome the obesity problem.